Portrayal of woman in contemporary Saudi poetry: an inductive study of samples of Saudi social themed poetry - Maryam Mohd Daud; Zamri Ariffin (Institut Kajian Rantau Asia Barat, 2010)
This study addresses the portrayal of woman in contemporary Saudi poetry in an effort to crystalize development aspects related to poetry with theme on women. Contemporary Saudi poets seem to show their profound interest in contemporary isssues on women, therefore it is undeniable there is a need to discuss portrayal of women when dealing with themes on Islamic religion and law. It seems that women occupies fundamental space of social and civilizational structure and developments, and society becomes weak and fragile unless it stands up on its firm footings in order to realize an intimate congruence and linkage between past and present. It can be summarised, through an analysis of a general picture, that a contemporary Saudi poet portrays and his Islamic tendency in exploring woman related themes of physical and spiritual aspects, and then an analysis of the works and their thematic classifications, that we can get hold of a clear picture of Saudi women the Saudi poets try to portray.